Β-1, 3-Glucan from Euglena gracilis as an immunostimulant mediates the antiparasitic effect against Mesanophrys sp. on hemocytes in marine swimming crab (Portunus trituberculatus). Issue 114 (July 2021) - Perveen, Summia; Yang, Lujia; Zhou, Suming; Feng, Bo; Xie, Xiao; Zhou, Qicun; Qian, Dong; Wang, Chunlin; Yin, Fei
Abstract: β-1, 3-glucans, natural polysaccharide groups, exert immunomodulatory effects to improve the innate response and disease resistance in aquatic species and mammals. However, this β-glucan stimulant is yet to be assayed in swimming crab ( Portunus trituberculatus ) hemocytes. In this study, we explored the immunomodulatory effect of β-1, 3-glucans (derived from Euglena gracilis) via in vitro 24 h stimulation assays in swimming crab hemocytes. We found that this algal β-1, 3-glucans in crab hemocytes significantly elevated cellular enzymes related parameters, including phenoloxidase (PO), lysozyme, acid phosphatase (ACP) activities, and superoxide anion generation (O2 − ) rate both at intracellular (P < 0.05) and extracellular (P < 0.05) levels. Besides, alkaline phosphatase (AKP) in hemocytes exhibited no significant differences across the groups (P > 0.05). β-glucan significantly influenced (P < 0.05) the activities of the antioxidant enzyme, superoxide dismutase (SOD) in hemocytes. Moreover, the relative mRNA expression of numerous immune-related genes, including proPO, TLR-2, Alf-1, NOX, Lysozyme, Crustin-1, and Cuznsod, was significantly higher stimulated hemocytes than in control (P < 0.05). We also reported the dose-dependent antiparasitic activity against Mesanophyrs sp., in stimulated hemocytes than in the control (P < 0.05). The present study collectively demonstrated that β-glucan potentially stimulates innate immunity by elevating cellular enzyme responses and up-regulating the mRNA expression of genes associated with crab innate immunity. Thus, β-glucan is a promising immunostimulant for swimming crab farming in crustaceans aquaculture. Highlights: β-glucan affects the immune parameters and gene expression in crab hemocytes. Stimulating hemocytes enhances immune activities and gene expression. Stimulated hemocytes have significant antiparasitic effects against Mesanophrys sp. β-glucan is a promising immunostimulant for swimming crab farming.